Theoretical Basis For The Evaluation Of Multi-Storey Housing - Adizova Farangiz Nurali qizi (Universitas Muhammadiyah Sidoarjo, 2022)
It should be noted that the sharp development of the urbanization process as well as the increase in the population significantly exceeds the demand for housing construction in the country. The optimal solution to this issue is the construction of multi-storey houses. It would not be an exaggeration to say that the housing reforms carried out today are evidence of this. Multi-storey houses are used not only to provide housing for the population , but also to radically change the appearance of cities and bring them to the level to which they can meet the modern demand. For this reason, the construction of multi-storey residences in our country is also gaining momentum.